2018
DOI: 10.3389/fmicb.2017.02680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Inoculum Levels of Multidrug-Resistant Salmonella enterica Serovar Heidelberg (2011 Ground Turkey Outbreak Isolate) on Cecal Colonization, Dissemination to Internal Organs, and Deposition in Skeletal Muscles of Commercial Turkeys after Experimental Oral Challenge

Abstract: Salmonella enterica serovar Heidelberg (S. Heidelberg) is a major foodborne pathogen colonizing poultry. The pathogen is associated with a significant number of foodborne outbreaks through contaminated poultry meat, including turkeys. Recently, multidrug-resistant (MDR) strains of S. Heidelberg have emerged as a threat to human public health in the United States. The objective of this study was to determine the cecal colonization, dissemination to internal organs, and the potential for skeletal muscle depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Comparative genomic analysis using Whole Genome Sequencing revealed that the S. Heidelberg isolates in the 2011 ground turkey outbreak clustered together when compared to isolates from human, animal, and retail meat sources ( Hoffmann et al, 2014 ). Using an experimental oral challenge experiment in turkey, a recent study showed that the Salmonella isolate causing the 2011 outbreak was high in cecal colonization, dissemination to internal organs, and tissue deposition ( Nair et al, 2018 ). Recently, a food-grade essential oil from pimento leaves was shown to reduce attachment of the 2011 S. Heidelberg isolate to turkey skin ( Nair and Johny, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomic analysis using Whole Genome Sequencing revealed that the S. Heidelberg isolates in the 2011 ground turkey outbreak clustered together when compared to isolates from human, animal, and retail meat sources ( Hoffmann et al, 2014 ). Using an experimental oral challenge experiment in turkey, a recent study showed that the Salmonella isolate causing the 2011 outbreak was high in cecal colonization, dissemination to internal organs, and tissue deposition ( Nair et al, 2018 ). Recently, a food-grade essential oil from pimento leaves was shown to reduce attachment of the 2011 S. Heidelberg isolate to turkey skin ( Nair and Johny, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A US poultry outbreak isolate of MDR SH was used in the study (GT2011; Nair and Kollanoor-Johny, 2017a , b ; Nair et al, 2018 ). Glycerol stocks of SH stored at −80°C were used for the preparation of working cultures.…”
Section: Methodsmentioning
confidence: 99%
“…Then the bacterial culture in PBS was serially diluted (1:10) to get a final concentration of 10 7 CFU ml −1 . From this, 100 μl was used in the experiments to inoculate the wells containing 2 ml TSB ( Kollanoor Johny et al, 2010 ; Nair and Kollanoor-Johny, 2017a , b ; Nair et al, 2018 ). For the in vivo study, GT2011 was made resistant to 50 μg ml −1 nalidixic acid sodium salt (NA; CAS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations